Meta-analysis of ontology software development process - A. Jabar, Marzanah; Khalefa, Mustafa Salah; Abdullah, Rusli; Abdullah, Salfarina (Praise Worthy Prize, 2014)
Ontology is an important concept in Computer Science to formally represent knowledge. The software engineering ontology assists in defining information for the exchange of semantic project information framework. Research into ontological issues has been widely active in various areas. This paper presents the origin of ontology research and gives the different definitions of ontology. The paper gives an overview of ontology and its types including the building and design for an enterprise system.This review tries to study articles in which adaption model and there properties were discussed in order to get a clear review about the ontology. This study is showed a Systematic Literature Review which was used to identify important characteristic about the ontology. The research identified more than 70 paper on this study but only 46 of them was precisely relevant in the field of Ontology development processs. In this paper we analyse the ontology based on types, design, building ,model as a systematic review of the subject.